2019
DOI: 10.7554/elife.47864
|View full text |Cite
|
Sign up to set email alerts
|

Proximity labeling of protein complexes and cell-type-specific organellar proteomes in Arabidopsis enabled by TurboID

Abstract: Defining specific protein interactions and spatially or temporally restricted local proteomes improves our understanding of all cellular processes, but obtaining such data is challenging, especially for rare proteins, cell types, or events. Proximity labeling enables discovery of protein neighborhoods defining functional complexes and/or organellar protein compositions. Recent technological improvements, namely two highly active biotin ligase variants (TurboID and miniTurbo), allowed us to address two challeng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(229 citation statements)
references
References 92 publications
6
190
0
Order By: Relevance
“…19 Our study demonstrates that TurboID is a powerful tool for dissecting signaling 20 networks. TurboID is also powerful for analyzing the proteomes of specific cell types and even 21 subcellular compartments in plants (Mair, 2019)(accompanying manuscript). Combining these 22 two applications, by expressing the TurboID fusion with signaling proteins using cell type- 23 specific promoters, will not only improve the sensitivity and specificity of the analysis but also illustrate signaling network in specific developmental context.…”
mentioning
confidence: 99%
“…19 Our study demonstrates that TurboID is a powerful tool for dissecting signaling 20 networks. TurboID is also powerful for analyzing the proteomes of specific cell types and even 21 subcellular compartments in plants (Mair, 2019)(accompanying manuscript). Combining these 22 two applications, by expressing the TurboID fusion with signaling proteins using cell type- 23 specific promoters, will not only improve the sensitivity and specificity of the analysis but also illustrate signaling network in specific developmental context.…”
mentioning
confidence: 99%
“…Next, we tested whether we could achieve biotinylation of protein interactors using PDL under the conditions established for N. benthamiana . We observed that the bait proteins used in plants for PDL so far were either membrane-anchored and small proteins [HopF2 (Khan et al, 2018) and AvrPto (Conlan et al, 2018)], or nuclear and/or cytoplasmic localized [OsFD2 (Lin et al, 2017), N (Zhang et al, 2019) and FAMA (Mair et al, 2019)].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two studies evaluated several generations of PBLs in plants, including the third generation TurboID and mTurbo using N. benthamiana and Arabidopsis seedlings as model systems and concluded that TurboID outperforms the other PBLs in its capacity of both cis -as well as specific trans -biotinylation of both known as well as novel target proteins under conditions compatible with normal plant growth (Mair et al, 2019; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high labelling efficiency and lower temperature requirement, TurboID and miniTurbo have been utilised to profile interaction networks in S. pombe, N. benthamiana, and Arabidopsis (Larochelle et al, 2019;Mair et al, 2019;.…”
Section: More Recently Branon Et Al Directly Evolved the E Coli Bimentioning
confidence: 99%
“…The two promiscuous variants TurboID and miniTurbo, have been reported to biotinylate proteins in the presence of biotin in mammalian cells, C. elegans, N. benthamiana and A. thaliana (Branon et al, 2018;Mair et al, 2019). To map the proteome of CTPS cytoophidium in Drosophila, the initial concern we had to address was that the filamentous structures of CTPS should not be affected under recombinant expression with TurboID or miniTurbo (hereafter called TbID or miniTb).…”
Section: Turboid-mediated Protein Biotinylation In Drosophilamentioning
confidence: 99%